The Effects of Subchronic Exposure to Metribuzin on Danio rerio. (18th June 2012) - Plhalova, Lucie; Stepanova, Stanislava; Praskova, Eva; Chromcova, Lucie; Zelnickova, Lenka; Divisova, Lenka; Skoric, Misa; Pistekova, Vladimira; Bedanova, Iveta; Svobodova, Zdenka
Abstract : The aim of this study was to assess the impact of metribuzin in surface waters on fish under experimental conditions. The effects of subchronic exposure to metribuzin on fish growth and the development of histopathological changes in selected organs (gill, kidney, liver) and on activity of some biochemical markers (CYP450, EROD) in Danio rerio were investigated during a 28-day toxicity test. Juvenile growth tests were performed on D. rerio according to OECD method number 215. Fish at an initial age of 30 days were exposed to a range of metribuzin concentrations (1.5, 5, 16, 33, and 53 mg L −1 ). Exposure to metribuzin at 53 mg L −1 was associated with increased mortality. Negative effects with regard to total body weight, length, and the inhibition of specific growth rate were induced at concentrations of 33 and 53 mg L −1 . Histopathological examination revealed pathological lesions in the liver in pesticide-exposed fish only at the highest concentration of 53 mg L −1 of metribuzin. Based on the results of growth rate, biochemical markers (CYP450, EROD), and histopathological examination, the lowest observed effect concentration (LOEC) value was 33 mg L −1 and the no observed effect concentration (NOEC) value was 16 mg L −1 .